2019
DOI: 10.5194/hess-23-1393-2019
|View full text |Cite
|
Sign up to set email alerts
|

Changes in groundwater drought associated with anthropogenic warming

Abstract: Abstract. Here we present the first empirical evidence for changes in groundwater drought associated with anthropogenic warming in the absence of long-term changes in precipitation. Analysing standardised indices of monthly groundwater levels, precipitation and temperature, using two unique groundwater level data sets from the Chalk aquifer, UK, for the period 1891 to 2015, we show that precipitation deficits are the main control on groundwater drought formation and propagation. However, long-term changes in g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 57 publications
1
49
0
2
Order By: Relevance
“…Groundwater drought, defined as below‐normal groundwater storage (Mishra & Singh, ), is mainly driven by long‐term precipitation deficit (Bloomfield et al, ; Eltahir & Yeh, ; Li et al, ). Bloomfield et al () also showed that thick capillary fringes in the unsaturated zone may have played a role in the increase in groundwater drought frequency in a warming world. These studies suggest that both climate and hydrogeological conditions may influence the evolution of groundwater drought.…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater drought, defined as below‐normal groundwater storage (Mishra & Singh, ), is mainly driven by long‐term precipitation deficit (Bloomfield et al, ; Eltahir & Yeh, ; Li et al, ). Bloomfield et al () also showed that thick capillary fringes in the unsaturated zone may have played a role in the increase in groundwater drought frequency in a warming world. These studies suggest that both climate and hydrogeological conditions may influence the evolution of groundwater drought.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these findings, the extent to which temperature and water availability will control ecosystem function in the future remains uncertain 4,5 . A recent study noted an increase in groundwater droughts coincident with hot periods in the 21st century (as opposed to only dry periods) and inferred that this shift was likely do to evaporative shifts with warming 6 . Higher temperatures increase evaporative demand, but how much this will induce moisture deficits and evaporative stress, as opposed to increased evapotranspiration, is partially dependent on climate [7][8][9] .…”
mentioning
confidence: 99%
“…This study used an idealised borehole in the Chalk of south-east England (Figure 2). Previous work has shown that in England climate change has already increased the frequency and intensity of groundwater droughts (Bloomfield et al, 2019) and is likely to result in future reductions in recharge and groundwater levels both on an annual basis and during seasonal minima (Jackson et al, 2015;Jackson et al, 2011;Watts et al, 2015). An idealised site was chosen as (1) the purpose of this research is to illustrate the methodology, and this ensures the approach is generic and can be applied across a range of future real-world examples from different types of fractured aquifers, and…”
Section: Study Areamentioning
confidence: 99%